Currently unavailable: for new students
Degree: Biomedical sciences (Bachelors) - Durham University
My name is Rosiered Brownson-smith and I study Biomedical Sciences at Durham University. I have a passion for science and maths! I pride myself on being friendly, enthusiastic and approachable- so don't hesitate to get in touch or book a 'Meet the tutor session'. I think there is nothing better than seeing a student grow and progress as they are helped along the way, as they begin to not only understand things but gain enthusiasm and confidence as they do.
What do I offer?
I offer tutoring the following subjects:
- A Level Biology
- GCSE Maths
- GCSE Psychology
Tutorial sessions with my will be tailored to each student. I ensure that each student fully understands each concepts and has complete confidence in using them in exam. There is nothing better than walking into an exam room not full of fear but confidence, that's why I will also always direct my sessions to exam techniques and skills as well as revision techniques that will help you all the way through your academic career.
I would also be happy to help with general essay writing skills and writing the dreaded personal statement.
But most of all I want to make learning FUN!- that is the best kind of revision technique.
I hope to hear from you soon :)
|Biology||A Level||£20 /hr|
|Before 12pm||12pm - 5pm||After 5pm|
Please get in touch for more detailed availability
The best way to solve a quadratic function is to put brackets into the equation.
Start with an example
Find x when y=0 for the function
y=x*2 + 5x + 6
As y=0 make the whole equation= 0:
x*2 + 5x + 6=0
Try and put this into brackets:
(x+a)(x+b)=0 (as all the values are positive, we know that there are going to be no negative signs in the brackets).
Now we just need to find values for a and b that multiply out to give us the equation we need.
Try a=6 and b=1:
This gives us the 6 at the end but when multiplied out gives us 7x- which is too much.
Now try a=2 and b=3 and multply out:
We get 0=x*2+ 2x + 3x + 6= x*2 + 5x + 6 ... which is what we want!
So we get (x+2)(x+3)=0
For it to equal 0 either:
x+2=0 so x=-2 or
x+3=0 so x=-3
so x=-2, -3see more